Report Cards : The Impact of Providing School and Child Test Scores on Educational Markets - Andrabi, Tahir; Das, Jishnu; Khwaja, Asim Ijaz (World Bank Group, Washington, DC, 2015)
This paper studies study the impact of providing school and child test scores on subsequent test scores, prices, and enrollment in markets with multiple public and private providers. A randomly selected half of the sample villages (markets) received report cards. This increased test scores by 0.11 standard deviations, decreased private school fees by 17 percent, and increased primary enrollment by 4.5 percent. Heterogeneity in the treatment impact by initial school quality is consistent with canonical models of asymmetric information. Information provision facilitates better comparisons across providers, improves market efficiency and raises child welfare through higher test scores, higher enrollment, and lower fees.